Safety of Strontium Chloride as a Skeletal Marking Agent for Pacific Salmon - Getchell, Rodman G (Journal of aquatic animal health, 2017)
The purpose of this study was to evaluate the biological effects associated with administering strontium chloride as a marking agent to age-0 Chinook Salmon Oncorhynchus tshawytscha fry. Fish were held in a 0× (0 mg/L), 1× (3,000 mg/L; current standard dosage), 3× (9,000 mg/L), or 5× (15,000 mg/L) solution of strontium chloride for 72 h (three times the standard duration of 24 h). The mortality among fish in the 5× strontium chloride exposure group was significantly higher than that observed in the other groups. A dose-related effect on general fish behavior and on feeding behavior was observed. Fish in all test tanks appeared to feed to satiation, except for fish in the 5× tanks during days 2 and 3. Fish in all other test tanks behaved normally. No dose-related effect on fish growth was detected. Histopathological evaluations showed that fish in the 5× exposure group had a significantly higher number of gill lesions than the 0× group. Our mortality, behavioral, and histological assessments suggested that juvenile Chinook Salmon could be safely immersed for three consecutive days in a 9,000-mg/L solution of strontium chloride. This finding potentially expands the present 1,000-3,000-mg/L dosage and 24-h holding period that can be used to mark juvenile fish with strontium chloride solutions. The research also provides necessary target animal safety data for U.S. Food and Drug Administration approval of strontium chloride as an alternative marking method that is suitable for fish with a short holding time. Received February 19, 2017; accepted July 16, 2017